The Use and Abuse of Social Capital in Social Science - Bhandari, Ravi; Fine, Ben (Himalayan Journal of Sociology and Anthropology, 2011)
In parallel with, and as complement to globalisation, social capital has enjoyed a meteoric rise in Sociology and across the social sciences in general over the last two decades. Not surprisingly, it has been particularly prominent across development studies, not least through heavy promotion by the World Bank. As a concept, though, as has been pointed out persistently by a minority critical literature, social capital is fundamentally lawed. Although capable of addressing almost anything designated as social, it has tended to neglect the state, class, power and conflict. As a buzzword, it has heavily constrained the currently progressive departure from the extremes of neo-liberalism and postmodernism at a time of aggressive assault by economics imperialism. Social capital should not be ignored but contested – and rejected. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4676 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 224-240